Numerical modeling of prefabricated vertical drain for soft clay using ABAQUS - Ahmad Tajuddin, Saiful Azhar (2014)
Construction, buildings and infrastructure founded on soft clays are often affected by settlement problem. Therefore, Prefabricated Vertical Drain (PVD) is one of the best solutions to accelerate soil consolidation by shortening the drainage path. In this study, numerical investigation was carried out to pursue a better understanding of the consolidation of soft clay improved with PVD. The consolidation process accelerated by vertical drains was analysed using the ABAQUS to create an elastic model with surcharge of 50 kPa. The aim of this study is to compare the settlement and the time required to consolidate the soft soil at different drain spacings (1.0m, 1.5m and 2.0m) for two different lengths of PVD. The results showed that the time required to consolidate the soft soil (100 % consolidation) at 12 m and 20 m length of PVD for different spacings are in the range of 3 months to 66 months. Rate of settlements are increasing with the decreasing of drain spacing for both lengths of PVD. For the excess pore water pressure at 12 m and 20 m length of PVD with different spacings, it can be concluded that the smaller design spacing, the time required for consolidation is also decreased